Impact Of Islamic Character, Information, And Innovation On Business Performance In The Tempe Industry - Nugroho, Moh Agus (Scimadly Publishing, 2022)
This study analyzes the influence of Islamic character, information, and innovation on business performance in the tempe industry. The research methodology used is quantitative research with a descriptive analysis approach. The results of the study explain that the Islamic character does not have a positive effect on the business performance of the tempe industry. Meanwhile, access to information and innovation on the business performance of the tempe industry has a significant positive effect. The access to information is the factor that has the biggest influence on business performance in the tempe industry. The implication of this research is to be able to develop micro, small and medium enterprises as well as efforts to support entrepreneurial progress, especially in empowering regional potential.